Functional aspects of BoT4+ alloreactive T lymphocytes transformed by Theileria parva - Teale, A.J.; Baldwin, Cynthia L. (1988)
The initial studies of the products of the bovine MHC with alloraective T lymphocytes generated in vitro have been described. In those studies, the cytolytic activity and specificity of bulk populations of alloreactive T cells were investigated. One non-cytolytic and two cytolytic BoT4 + clones were studied following in vitro infection and transformation with sporozoites of T. parva. In this paper, the results of this study are also discussed. According to the results, transformation of bovine alloreactive T lymphocytes has the advantage that derived cell lines do not require repeated exposure to antigen and the addition of exogenons growth factors during culture and thus are simple to maintain in a functional state.